Pre-Emptive Dexamethasone for Managing Post Operative Pain in Patients Undergoing Laparoscopic Cholecystectomy Under General Anaesthesia: A Prospective Randomized Study - Savneet Sasan; Sunana Gupta; Ranika Devi Manhas; K. S Mehta; Asrar Mustafa (Dr. Annil Mahajan, 2024)
Background: Pain after laparoscopic cholecystectomy arise from multiple sources and so require multimodal approaches to manage it. Dexamethasone is a corticosteroid drug with excellent anti-inflammatory properties. Present study was designed to study the effect of administering an intermediate dose of dexamethasone (8 mg), one hour before the induction of anaesthesia, on post-operative analgesia, time to first analgesia and total number of analgesics used in twenty-four hours. Material and Methods: A total of 80 patients were randomly allocated into two study groups by computer generated randomization. Group 1 received 8 mg/2 ml of Inj. Dexamethasone intravenously 1 hour prior to induction of General Anaesthesia slowly over a period of 5 minutes. Group 2 received 2 ml of Normal Saline (NS) intravenously 1 hour prior to induction of General Anaesthesia slowly over a period of 5 minutes. Results: The mean Visual analogue score of group 1 was lower than that of group 2 and the difference was statistically significant at 0, 2, 6 and 12 hours postoperatively (p<0.05). The mean time taken by the patients in group 1 for the first rescue analgesic was (11.65±4.59) hours, which was statistically significant as compared to group 2 (4.01±2.03) hours(p=0.0001). Mean total number of analgesic used in Group I was significantly less as compared to Group 2 (p=0.0001) Conclusion: Use of dexamethasone 8 mg intravenously one hour before induction of general anaesthesia for post-operative analgesia causes a significant decrease in overall VAS score at 0, 2, 6 and 12 hours post-operatively, increases the duration between the surgery and the need for first rescue analgesia and decreases the total number of analgesics used with minimal adverse effects after laparoscopic cholecystectomy